Use of pectoralis major fascia in dorsal nasal augmentation: case report - Camila Matos Versiani; Lucas Silva Couto; Andreia Souto da Motta; Marcus Vinícius Capanema Gonçalves; David Santiago Ordonez Arizaga; Klaus Rodrigues de Oliveira; Waldemar Chaves Nascimento Brandão Penna; Sérgio Moreira da Costa (Revista Brasileira de Cirurgia Plástica)
Increasing the nasal dorsum in rhinoplasty is the focus of several studies that seek the best graft sources and surgical techniques. The use of cartilage from the nasal septum, ear shell, or costal arches is already established for this purpose. In recent years, methods have been sought to reduce the palpability and dispersibility of cartilaginous grafts. Thus, synthetic materials such as SURGICEL® and autologous materials such as fascia have been explored. Temporal fascia are more widely used but require a new surgical incision, increasing surgical time and morbidity. Also described is the use of fascia lata and rectus abdominis fascia, which are comparatively thicker and less flexible. In many rhinoplasty procedures, it is necessary to remove the costal cartilage, which allows the collection of fascia from the major chest muscles through the same surgical incision. Thus, we describe the use of major chest muscle fascia and chopped costal cartilage in structured rhinoplasty to increase the dorsum.